Evaluation of the quality of medical care in cases of death from acute blood loss (according to data of forensic-medical examinations) - Pletenetska, A.O.; Demchenko, I.S.; Ergard, N.M. (Medicni Perspektivi, 2021)
The peculiarities and specificity of the medical field complicate not only the assessment of quality and timeliness of medical care, but also the correctness of the choice of the method of treatment and diagnosis of the disease. The number of forensic medical examinations in «medical cases» has the tendency to increase, and experts in this case face difficulties with forensic medical assessment of medical care provision. Forensic medical analysis of the medical care provision to patients who died of acute blood loss, based on examinations of different forensic medical bureaus of Ukraine has been analyzed. The aforementioned examinations related to the corpses of people who died as a result of acute blood loss, including shock (150 from the total number of 6129 medical examinations were selected). This cause of a death was chosen as one of the leading causes of death in trauma (including a combination with shock). When evaluating gross medical care defects that were found during the examinations that influenced the result, 40.0% (60) – in the form of improper provision (action) were noted in 10 cases (the case of incorrect diagnosis made by the doctors due to underestimation of examination data), defects in the form of non-provision of medical care (inactivity) – in 83.3% (15 cases). In the statistical analysis of defects in the provision of medical care, the majority of cases were connected with delayed provision of medical care – 41,7%. Defects in cases of blood loss were under the following conditions: a) lack of instrumental research, medical treatment and surgery, b) lack of medical treatment and surgery by indications (each of 3,3%). When considering the reasons that led to defects in cases of blood loss, the isolated underestimation of the examination data was in 16,7% (25), a combination of reasons: a) underestimation of the examination data together with the underestimation of additional research data – 16,7% (25); b) underestimation of the examination data together with the negligent attitude to the patient who had a sloppy appearance – 6,7%. The unprofessional nature of the medical staff was in 16,7% of acute blood loss. When providing medical care in cases of death from acute blood loss, defects in the provision of medical care are made by experienced medical professionals in city hospitals (especially large cities of Ukraine), where there are adequate conditions for the provision of medical care, more qualified specialists of different profiles, and there are protocols for providing medical care in acute blood loss.